Regresi Logistik Biner dalam Menentukan Pengaruh Kualitas Pelayanan Terhadap Kepuasan Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Surabaya - Nikie Ramsi Tamnge (Universitas Muhammadiyah Surabaya, 2016)
Quality of service is seen as one of the tools to achieve a competitive advantage because it is one of the factors that determine the selection something that can satisfy the students. Student satisfaction will be achieved if the quality of services provided according to needs. Student satisfaction itself can be defined as a student feeling after comparing the perceived outcome with expectations. This study aimed to determine the effect of service quality of BAAK on student satisfaction FKIP Muhammadiyah University of Surabaya. This study used quantitative descriptive design. The samples were taken from FKIP students proportionally in each department. There were five explanatory variables used in this study, namely: tangible (????1), reliability (????2), responsiveness (????3), assurance (????4), and emphaty (????5). While the response variable is student satisfaction (????). Based on the partial test using binary logistic regression, it was known that the five explanatory variables were variables that influenced individual student satisfaction.